Performing Authorship Strategies of »Becoming an Author« in the Works of Paul Auster, Candice Breitz, Sophie Calle, and Jonathan Safran Foer - Longolius, Sonja (Edition Kulturwissenschaft, 2016)
Authors not only create artworks. In the process of creating, they simultaneously bring to life their author personae. Approaching this phenomenon from an interdisciplinary point of view, Sonja Longolius develops a concept of »performative authorship« by examining different strategies of becoming an author. In regard to the notion of her concept, this work offers a critical and comparative analysis of the works of Paul Auster, Candice Breitz, Sophie Calle, and Jonathan Safran Foer. Specifically, Auster/Calle and Breitz/Foer form a generational pair of opposites, enabling a discussion of postmodern and post-postmodern artistic strategies of »performative authorship«